2017
DOI: 10.18261/issn.1891-1838-2017-02-05
|View full text |Cite
|
Sign up to set email alerts
|

Et maktperspektiv på «gode nok foreldre» i barnevernets kontekst

Abstract: SammendragArtikkelen tar utgangspunkt i uttrykket «gode nok foreldre» som barnevernsarbeidere i forskningsstudien «Fra tanker til teori: En studie om barnevernsarbeideres resonnering» bruker når de snakker om de barnevernfaglige vurderingene som de foretar. Dette begrepet er også anvendt i flere sammenhenger innenfor barne-og familieområdet, som for eksempel i dommer, faglitteratur og forskning. Det faktum at begrepet benyttes i ulike sammenhenger, har ikke bidratt til å klargjøre begrepet naermere betydning. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…What constitutes a “good enough’ family in child welfare case work is oftentimes vague and unclear (Choate and Engstrom, 2014; Langsrud et al, 2017). The study shows how a given culture’s shared meaning of family impacts practice within participatory processes.…”
Section: Concluding Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…What constitutes a “good enough’ family in child welfare case work is oftentimes vague and unclear (Choate and Engstrom, 2014; Langsrud et al, 2017). The study shows how a given culture’s shared meaning of family impacts practice within participatory processes.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…There have been multiple calls for studies showing the ambiguities and complexities involved in children's participation in these contexts, especially with regard to family (Tisdall and Punch, 2012;Spyrou et al, 2019;Horgan et al, 2017). Moreover, limited research explores social workers' views of children's situations in child welfare with a focus on family relations (Jensen et al, 2019), and there is a knowledge gap regarding how familial relationships and a "good enough" family are defined in the professional field of child welfare case work (Choate and Engstrom, 2014;Langsrud et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As these researchers have pointed out, women of limited means and having few privileges are seldom able to reach this ideal. As studies of the Norwegian child welfare system have shown, assessments of parental competence draw on attachment theory, emotional care, and risk perception [36,37]. This mother's experience with the CPS shares features with cases raised in recent years against the Norwegian child welfare system at the European Human Rights Court (EHRC) in Strasbourg, France [38].…”
Section: Analyzing the Casementioning
confidence: 99%
“…L 106 (2012-2013), Barne-likestillingsog inkluderingsdepartementet (2013), følger det at foreldreomsorgen bør ivareta barnet på en slik måte at dets livssituasjon er innenfor det som regnes for å vaere en normal oppvekst for barn flest. Normalitet ved barnets oppvekstbetingelser og utvikling var også gjenstand for økt oppmerksomhet fra barnevernvernsarbeiderne i denne studien (Langsrud, Fauske & Lichtwarck, 2017). En «normal» oppvekst vil statistisk sett kunne bli relatert til en middelklasseoppvekst med dens tilhørende normalvariasjon.…”
Section: Foreldrenes Rammer For Omsorgsutøvelsenunclassified